2013
DOI: 10.1098/rstb.2011.0327
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the matriline for genomic imprinting, brain development and behaviour

Abstract: Mammalian brain development commences during foeto-placental development and is strongly influenced by the epigenetic regulation of imprinted genes. The foetal placenta exerts considerable influence over the functioning of the adult maternal hypothalamus, and this occurs at the same time as the foetus itself is developing a hypothalamus. Thus, the action and interaction of two genomes in one individual, the mother, has provided a template for co-adaptive functions across generations that are important for mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
1
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 90 publications
0
37
1
1
Order By: Relevance
“…In animals, genomic imprinting is only known in therian mammals, and most imprinted genes are expressed and imprinted in the brain and placenta (Pask, 2012;Keverne, 2013;Renfree et al, 2013). Having the full catalog of imprinted genes in several different mammalian species will greatly facilitate the understanding of many evolutionary questions about genomic imprinting, including but not limited to origin and fixation of genomic imprinting, conservation of degree of expression direction and imprinted genes, dynamic gain and loss of imprinting status on the mammalian phylogenetic tree and effect of loss of diploidy for imprinted genes in shaping the population genetic profile.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, genomic imprinting is only known in therian mammals, and most imprinted genes are expressed and imprinted in the brain and placenta (Pask, 2012;Keverne, 2013;Renfree et al, 2013). Having the full catalog of imprinted genes in several different mammalian species will greatly facilitate the understanding of many evolutionary questions about genomic imprinting, including but not limited to origin and fixation of genomic imprinting, conservation of degree of expression direction and imprinted genes, dynamic gain and loss of imprinting status on the mammalian phylogenetic tree and effect of loss of diploidy for imprinted genes in shaping the population genetic profile.…”
Section: Introductionmentioning
confidence: 99%
“…As the foetus is developing its own hypothalamus at this time period, a developmental template is available on which selection pressures may operate within a generation with functional consequences across two generations (Figure 2). Thus, an infant who has received optimal nourishment and care will itself be both energetically equipped and genetically predisposed to good mothering in the next generation (Keverne, 2012). Molecular genetic studies have identified several of the imprinted genes, which are co-expressed in the developing hypothalamus and placenta, to be concerned with regulation of maternal behaviour and physiology (Keverne, 2012).…”
Section: Genomic Imprinting and Maternal Foetal Co-adaptationmentioning
confidence: 99%
“…Thus, an infant who has received optimal nourishment and care will itself be both energetically equipped and genetically predisposed to good mothering in the next generation (Keverne, 2012). Molecular genetic studies have identified several of the imprinted genes, which are co-expressed in the developing hypothalamus and placenta, to be concerned with regulation of maternal behaviour and physiology (Keverne, 2012). Detailed studies with mice carrying a mutation in the maternally imprinted gene (Peg3) have provided some insights into how the functioning of the hypothalamus, which develops in utero, is adapted to respond to the placental hormones that determine maternalism.…”
Section: Genomic Imprinting and Maternal Foetal Co-adaptationmentioning
confidence: 99%
See 2 more Smart Citations